THE PRINCIPAL AS A PIONEER, IMPROVING TEACHER PROFESSIONALITY AT SMP IT NURUL BAROKAH CIKIJING, MAJALENGKA REGENCY - Abdillah, Atep Nur (ASWAJA: Jurnal Pendidikan dan Keislaman, 2025)
This study aims to analyze the principal's management in improving teacher professionalism at Nurul Barokah Cikijing Islamic Junior High School, Majalengka Regency. Teacher professionalism is a key factor in determining the quality of education, therefore the principal's role as an educational manager is crucial to ensuring optimal learning. This study used a qualitative approach with a case study method, where data were collected through interviews, observation, and documentation. Data analysis was conducted descriptively through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that the principal carries out management functions that include integrated planning, organizing, implementing, and supervising to improve teacher professionalism. Planning is carried out through the development of work programs based on teacher and school needs. Organization is carried out by placing teachers according to their competencies and areas of expertise. Implementation is carried out through providing motivation, supervision, training, and rewards to teachers. Meanwhile, supervision is carried out through periodic evaluations of teacher performance, both individually and collectively. This study also found that supporting factors for improving teacher professionalism include internal teacher motivation, discipline, and supporting infrastructure. The challenges faced include a limited number of certified teachers, poor time management, and minimal use of learning technology. Therefore, it can be concluded that educational success is largely determined by the principal's ability to effectively manage human resources, enabling teachers to improve their pedagogical, professional, personal, and social competencies.